ANALISIS FAKTOR-FAKTOR PENYEBAB KESULITAN SISWA DALAM MENULIS KARANGAN NARASI PADA PEMBELAJARAN BAHASA INDONESIA KELAS III DI SDN 21 SEMBAWA - Putri Anjelita; Rury Rizhaldi; Bambang Hermansah (STKIP Subang, 2023)
ABSTRACT The purpose of this research is to find out the factors that cause students' difficulties in writing narrative essays in class III Indonesian language learning at SDN 21 Sembawa. The method used in this research is descriptive qualitative. The informants who were the subject of this study were teachers and third grade students at SDN 21 Sembawa. Data collection techniques used in this study were observation, interviews, questionnaires and documentation. The data obtained from the research were then analyzed qualitatively and described in a qualitative descriptive form. The results of this study indicate that students' difficulties in writing narrative essays are based on indicators of writing essays, students still have difficulties in indicators of idea content, namely adjusting the title to the content. In terms of content organization indicators, some of the students' essays did not really match the content with the essay titles, and it was seen that the students' essays were still not optimal, the ideas made by students had not been developed properly. In the grammar indicators, there were many student errors in composing words in essays, mistakes in writing word and sentence structures and there were some words that were difficult to understand. On style indicators: choice of structure and diction, namely the vocabulary used by students is still limited, students still repeat the same words a lot. Spelling and punctuation indicators, errors in capitalization, and use of periods and commas. Factors that cause student difficulties are internal factors which include: student attitudes in learning activities and student motivation in learning, study habits carried out by students in class and at home. External factors consisting of the teacher's method of teaching in the classroom as well as the family and community environment.